2014
DOI: 10.17051/io.2014.24751
|View full text |Cite
|
Sign up to set email alerts
|

Basında Yer Alan Okullarda Şiddet İle İlgili Olayların Değerlendirilmesi

Abstract: ABSTRACT.This research was carried out to examine the place of the concept of violence in schools as one of the major problems in social life and how the violence-related news reflects in a variety of newspapers. In this study, questions were searched for the answer about: how the news headlines containing violence in schools are given; how the definitions and notions used in school-related violent headlines are given; which pages the reports of violence are published in; how the pictures used in violent news … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…Çubukçu ve Dönmez (2012) revealed that the types of violence at school are fighting, threatening and swearing. Teyfur (2014), in his research, showed that the stabbings at school has reached from 1,49% to 4,23, which is parallel with our results.…”
Section: Types Of Violencesupporting
confidence: 91%
See 1 more Smart Citation
“…Çubukçu ve Dönmez (2012) revealed that the types of violence at school are fighting, threatening and swearing. Teyfur (2014), in his research, showed that the stabbings at school has reached from 1,49% to 4,23, which is parallel with our results.…”
Section: Types Of Violencesupporting
confidence: 91%
“…When the news regarding verbal violence is analyzed, the behaviors such as threatening, insulting, and humiliation come to the forefront (Teyfur, 2014).…”
Section: Drawing 8 (M;9)mentioning
confidence: 99%
“…The acts of violence at primary schools has been classified as physical, sexual, and verbal-written within this study. It has been observed in other studies in the literature that violence acts at schools are mostly physical, verbal and sexual (Çınkır & Kepenekci, 2003;Teyfur, 2014). Espelage, Anderman, Brown, Jones, Lane, McMahon, Reddy and Reynolds (2013) have stated that violence acts at schools are of verbal or non-verbal menace and physical violence.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 94%
“…Inadequacy of education in school and exhibition of violent behaviors by individuals who are taken as an example in school, which are stated to be among the problems leading to school violence, are consistent with the views of the The way the obstacles emerging in the problem-solving process are overcome + school administrators participating in the present study. Based on the news about events of violence appearing on media, the results of another research show that teachers' attitudes ranked first among the causes of school violence in 1998, but they were replaced by parents' attitudes and socio-economic problems in 2004 (Teyfur, 2014). The solution school administrators adopt most when an event of violence takes place in their school is stated to be directing the students involved in the events of violence to the school's psychological counselling and guidance service.…”
Section: Discussionmentioning
confidence: 99%